2017
DOI: 10.1590/1982-3533.2017v26n4art8
|View full text |Cite
|
Sign up to set email alerts
|

Estado e financeirização no Brasil: interdependências macroeconômicas e limites estruturais ao desenvolvimento

Abstract: Resumo A compreensão das relações Estado-economia é uma etapa necessária da análise das condições que bloqueiam o desenvolvimento brasileiro. O regime de crescimento econômico que emergiu das transformações estruturais da década de 1990, e subsiste até a atualidade, caracteriza-se por seu baixo dinamismo e instabilidades conjunturais recorrentes. Estudos recentes classificam-no entre os regimes dominados pelas finanças que, em função da situação externa e da política econômica vigente, ora assume um caráter fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…As Rangel stated (1981: 32), at the core of this discussion, “the financial issue is an institutional problem,” in the sense of being ultimately in the realm of the political economy. The financialization is the outcome of institutional reforms that enable the extraction of social wealth (Paulani 2017; Bruno and Caffe 2017; Lavinas, Araújo, and Bruno 2019; Bresser-Pereira, Paula, and Bruno 2020; Carneiro 2020). Rangel is also supported by the neo-Schumpeterians because, as pointed out by Peréz (2010a), the financial sector activities enhance disruptive technological development.…”
Section: Ignacio Rangel and The Brazilian Fourth Dualitymentioning
confidence: 99%
See 2 more Smart Citations
“…As Rangel stated (1981: 32), at the core of this discussion, “the financial issue is an institutional problem,” in the sense of being ultimately in the realm of the political economy. The financialization is the outcome of institutional reforms that enable the extraction of social wealth (Paulani 2017; Bruno and Caffe 2017; Lavinas, Araújo, and Bruno 2019; Bresser-Pereira, Paula, and Bruno 2020; Carneiro 2020). Rangel is also supported by the neo-Schumpeterians because, as pointed out by Peréz (2010a), the financial sector activities enhance disruptive technological development.…”
Section: Ignacio Rangel and The Brazilian Fourth Dualitymentioning
confidence: 99%
“…1 In recent years, interest is resurgent about heterodox ideas, especially in face of the neoliberal stumbling performance of policies. Several points of view are gauged by “structural” or “social” developmentalist approaches (see Bruno and Caffe 2017; Paulani 2017; Lavinas, Araújo, and Bruno 2019; Bresser-Pereira, Paula, and Bruno 2020; Carneiro 2020), and endorse the process of "financialization" at the core of the Brazilian crisis. Also, greater scrutiny about Rangel's theoretical contributions is evolving in current conditions (A.P.C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing the Brazilian State in face of the structural transformations (internal and external) of the 1990s, authors such as Teixeira and Pinto (2012); Bruno and Caffé (2017), reflect that as a regulatory and organizing instance of capitalist development in a particular way, the State seeks to meet the interests of certain social classes and/or economic sectors, which manifest their hegemony through particular forms of legitimization. Furthermore, according to these authors, it acts as an articulating instance of the national economic and territorial space with the world capitalist system.…”
Section: Graph 1 -Amount Issued In Certified Green Bonds -Brazil and Chinamentioning
confidence: 99%
“…According to Carvalho and Vidotto (2007), after the mid-1990s, there was an expansion of foreign capital in the Brazilian banking and infrastructure sectors (Campos, 2018). Bruno and Caffe (2017) reported that the growth of the financial flow in the Brazilian economy occurred mainly in the 1990s. In the intra-corporate context, studies such as those developed by Miranda, Crocco, and Santos (2017) and Moraes (2017) converge when identifying business practices aligned with the financial logic and the maximization of shareholder value in the national corporate context.…”
Section: Introductionmentioning
confidence: 99%